Role of altered gut microbiota in the development of obesity, insulin resistance and type 2 diabetes mellitus - Shrestha, UK (Nepal Journal of Medical Sciences, 2013)
Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 1-2 DOI: http://dx.doi.org/10.3126/njms.v2i1.7642